EXOGENOUS FACTORS OF RHYTHMIC GYMNASTICS DEVELOPMENT IN MODERN CONDITIONS - Morozova L.V.; Bystrova I.V.; Ponimasov O.E. (Theory and Practice of Physical Culture, 2024)
Objective of the study is the methodological substantiation of external factors of influence that determine the direction of the pedagogical algorithms of the training process in rhythmic gymnastics at the present stage of sports development. Methods and structure of the study. A meta-analysis of a vast amount of information obtained by researchers and specialists in the field of rhythmic gymnastics was carried out by combining data into a single set of information array with subsequent correlation, regression analysis and approximation of the data obtained. r-indices were chosen as indicators for evaluating the results. The interpretation of the obtained effect was carried out in the context of a separate study in comparison with previous studies. Results and conclusions. Identification of factors of external influence proves the prospects of pedagogical corrections of the training process of female athletes at the present stage of development of this sport. Taking into account the influence of external factors on the training process in rhythmic gymnastics is manifested in a decrease in the volatility of sports training through the systematic solution of multifactorial problems of technical training of gymnasts.